Curcuma longa and Boswellia serrata extract combination for hand osteoarthritis: an open-label pre-post trial - Yves Henrotin; Yvan Dierckxsens; Gaëlle Delisse; Nathalie Maes; Adelin Albert (Taylor & Francis Group, 2022)
Context Osteoarthritis (OA) of the hand is a common painful musculoskeletal disorder with no cure. There is a need for an efficient and safe treatment to relieve OA pain.Objective To investigate the effects of a Curcuma longa and Boswellia serrata food supplement in addition to standard care on hand pain.Materials and methods This open-label, non-controlled, post-observational study was based on 232 patients suffering from hand pain with or without joint deformity. Patients received a medical prescription for a three-month treatment with a food supplement containing 89 mg of C. longa dry extract, 120 mg of B. serrata resin, and 1.8 µg vitamin D. Pain was evaluated on a 10-point visual analog scale (VAS). The number of painful hand joints, patient satisfaction, nonsteroidal anti-inflammatory drugs intake, and side effects were also recorded.Results Baseline pain intensity (regression coefficient ± SE: −0.19 ± 0.01, p < 0.0001) and the number of painful joints (regression coefficient ± SE: −0.022 ± 0.0029, p < 0.0001) decreased significantly throughout the 3 months treatment period. NSAIDs intake and topical drug application were significantly decreased by 64% (p < 0.0001) and 79% (p < 0.0001) after 12 weeks, respectively. Only 3/239 (1.3%) patients reported side effects probably related to the product. 80.3% were satisfied with the treatment and 75.5% wished to continue treatment.Conclusion This is the first clinical trial showing that C. longa and B. serrata resin can relieve symptoms in patients with hand osteoarthritis. The study provides useful information for the design of a clinical trial including a broader population.